Результати голосування щодо “української” резолюції в ГА ООН як індикатор особливостей сучасного балансу сил у світовій політиці - Турчин, Ярина (Lviv Polytechnic National University, 2015)
Розглянуто вплив українсько-російського конфлікту на сучасний стан світового порядку. Продемонстровано особливості розв’язання “української кризи” на рівні багатосторонньої дипломатії, передусім Генеральної Асамблеї ООН. За допомогою методу зіставлення досягнуто основної мети дослідження – виявлено особливості сучасного процесу трансформації світового балансу сил. Зроблено висновок про те, що приймаючи рішення щодо голосування “української” резолюції ГА ООН, кожна країна здебільшого керувалася власною ідеологією чи інтересами урядів, а не реальною ситуацією в Україні чи проблемами глобального значення. The impact of the Ukrainian and Russian conflict on the modern state of world order and the efficiency of global security system was dwelled upon. The peculiarities of solving this conflict on the level of multilateral diplomacy, namely at UNGA, which corresponds to international practice, were demonstrated. The benchmark method was applied to achieve the main objective of the research: to reveal characteristics of modern transformation of power balance and to define the role of Ukraine. It was concluded that, when taking the decision on “Ukrainian” resolution, each country was guided by its own ideology or its government’s interests, not by the current situation in Ukraine or problems of global importance. The Ukrainian and Russian conflict provoked the beginning of revising the state of world order and bipolar global power balance with the union of the USA and the EU on one side and authoritarian Russia on the other side. Meanwhile, Japan took the waiting position, hoping for the maximum benefit from opposition between Russia, the USA and the EU. In.0 such multiparty dialogue between key players, the USA, the EU, Russia and Japan, it is important for Ukraine not to become a pawn in the game of fulfilling other’s geopolitical ambitions, but to strengthen its status as an independent and. influential subject of international relations with strong internal and foreign policy. The urgent need in revision of Ukrainian foreign policy on the whole is pointed out. Firstly, it is necessary to promote cooperation with counties of Africa, Asia and South America, which for many years had been underestimated by Ukrainian authorities. Secondly, it is worth taking into account that Russia currently is trying to enforce its influence on post-Soviet countries where there are critical problems with developing a consolidated democracy, as well as stability of political and economic systems. Due solving of Ukrainian conflict will also restore the capacity of the international law and reinforce the role of the UNO in a system of international relations in the globalized 21st century.
Voting results on “Ukrainian” resolution at unga as an indication of modern power balance peculiarities in the world politics
Keywords: Україна; Російська Федерація; конфлікт; голосування; Генеральна Асамблея ООН; Ukraine; the Russian Federation; conflict; voting; UNGA